Emerging Organizations: In Between Local Translation, Institutional Logics and Discourse - Susanne Boch Waldorff (Copenhagen Business School (CBS), 2010)
In this dissertation I focus on a national reform of the Danish public sector, which in January 2007 facilitated the development of new municipal health care centers in order to meet specific local demands and to improve primary health care. However, this new organizational concept was not presented as a mandatory and detailed legislative reform. The municipalities therefore developed centers focusing in different ways on health promotion and rehabilitation and with great variation in their structure. Specifically, I find it intriguing how specific actors at the local level, such as politicians, medical professions, and social welfare professionals, were able to participate in local developments, and how they constructed specific organizational forms as local manifestations of the new national policy. Particularly, I am interested in exploring how the heterogeneous institutional context influences local actors' translation of an abstract organizational concept into specific organizational forms....
hdl:10398/8021
Keywords: 650